PEMBINAAN EKSTRAKURIKULER SEPAK BOLA DI SMP NEGERI 29 PEKANBARU - Ryan Hasmary; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is the lack of support from the director for extracurricular activities, the lack of support from parents and the lack of availability of facilities and infrastructure. The purpose of this research was to determine the director's support, the quality of the coach and the extracurricular football infrastructure at SMP Negeri 29 Pekanbaru. The population in this research was 20 students engaged in extracurricular activities. The sampling technique was total sampling. The tool used in this research was a questionnaire. The data obtained was analyzed using the% percent test technique. Based on this research analysis of school institutions with a bad category, namely with the following details: 0% or as many as 0 respondents are classified as strongly agree, 50% or 10 respondents are classified as agree, 45% or 9 respondents are classified as disagree and 5% or 1 respondent classified as strongly disagree. in extracurricular football coaching at SMP Negeri 29 Pekanbaru he has sufficient technical command and experience. Of the 20 existing athletes, 19 (95%) are of good quality and 1 coach is of good quality. The facilities and infrastructure for extracurricular football development at SMP Negeri 29 Pekanbaru were good.Key Words: Athlete Development, Coach Quality, School Institution, Football